Mineralogical and isotopic data of freshwater cultured pearls from Kentucky Lake with associated lake environmental data - Gabriela Farfan; Chunhui Zhou; Ian Orland; John W Valley (PANGAEA, 2021)
This dataset for our publication (Farfan et al, 2021) combines high spatial-resolution mineralogical and isotope data of freshwater cultured pearls with the environmental conditions of the lake in which they grew under (Kentucky Lake, TN). SIMS-based δ18O values were taken for six transects across three pearls (mirroring transects A and B for each pearl). Detailed mineralogical analyses in the form of nacre tablet thickness (sub-micron) and Raman spectroscopy data of the carbonate vibrational modes of nacre aragonite are calculated for positions along the pearls corresponding to the transects of SIMS-made pits. The corresponding Kentucky Lake environmental data is translated into pearl-nacre space along the same SIMS pits and estimated based off of raw data from the Kentucky Lake Long-Term Monitoring Program run by Murray State University, KY. Any researchers interested in the raw Kentucky Lake data must contact this program directly.